Praktyki studenckie jako pierwszy krok rozwoju zawodowego – refleksje na przykładzie praktyk pedagogów szkolnych - Farnicka, Marzanna; Koch, Astina (Adult Education Discourses, 2020)
The article deals with the problem of the importance and effectiveness of student internships from perspective of students. Teaching practice is one of the most important elements of pedagogy. The pentabase model was adopted as the method of analysis, which allows the presentation of selected problems in terms of time, space, commitment and information. These categories were considered possible to use in the process of preparing and evaluating student internships. Based on the student placement journal, significant problem areas were identified using the compliance method of competent judges. The results of the analyses of student experiences indicate discrepancies between expectations and experience gained during internships in terms of their organisation, commitment and information. The revealed areas of conflict allow for reflection and specific actions to be taken among internship organisers and mentors , they also instigate reflections on the professionalisation of the first professional experience.